Labour Reform and top executives of public companies. Brief overview of the new legal framework (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
During year 2012 some rules have been published regulating the legal framework of the public companies top executives mainly in their rights arising from the terminationof the contract as well as the structure of their remuneration package. This implies a significant legislative change whose aim is to regulate and provide with more transparency the contractual conditions of the aforementioned collective. The latter has seen how in a short period of time, its commercial or labour contracts have been adapted to the new regulation implying, in some cases, some limits to the rights they were entitled to before.
Keywords: Public company; Top executive; Director; Remunerations; Indemnifications; Dismissal.